Developing e-learning media in grammar instruction for beginner learners - Afidah, Nurul; Hanifah; Alkhoyyath, Dliyauddin (Universitas Muhammadiyah Sidoarjo, 2021)
The present study intended to develop E-learning media in teaching grammar for beginner learners. In developing the product, this study adapted the ADDIE model. The product that was developed using construct application focused on part of speech material. Thirty students of sixth grade enrolled on the implementation phase. Before implemented the product, some experts gave some suggestions and critics related to the quality of the product. The final product consists of some explanations of part of speech along with exercises, and in each exercise it is provided direct feedback whether the answer is right or wrong. On the first slide, a cover is displayed with attractive and colorful background since the target learner is beginner. The language used in this product is fully in English to habituate the learners with English environment. For the back sound, the researcher used rhythm only, not a song to avoid disturbing the learners. The researcher provides learning objectives. In this case there are three learning objectives. Then on the next slide it is showed eight part of speech that will be explained in detail. In material the researcher provided the definition and kinds of part of speech, also the example of part of speech. Moreover, the exercises were created in various types, ten questions in multiple choice and five questions in jumble word. This media can be used by anyone who needs it, and another researcher can develop similar media in different topic or level. HIGHLIGHTS: E-learning media that is implemented optimally can help the teacher in achieving learning objectives. E-learning media can be used as an alternative media during class instruction especially grammar instruction. In this digital era, the teacher is demanded to habituate to use e-learning media during class instruction.